2021
DOI: 10.1007/s11367-021-01904-2
|View full text |Cite
|
Sign up to set email alerts
|

Life cycle assessment of bacterial cellulose production

Abstract: Purpose Bacterial cellulose (BC), obtained by fermentation, is an innovative and promising material with a broad spectrum of potential applications. Despite the increasing efforts towards its industrialization, a deeper understanding of the environmental impact related to the BC production process is still required. This work aimed at quantifying the environmental, health, and resource depletion impacts related to a production of BC. Methods An attributional life cycle assessment (LCA) was applied to a process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Forte et al [ 43 ] note that the manufacture of BC by using individual strains under production environments is quite limited, whereas the production of BC by using symbiotic cultures is traditionally widely practiced in the Asian-Pacific Region. The production of BC by a using symbiotic culture currently continues to broaden, including that for technical applications [ 25 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Forte et al [ 43 ] note that the manufacture of BC by using individual strains under production environments is quite limited, whereas the production of BC by using symbiotic cultures is traditionally widely practiced in the Asian-Pacific Region. The production of BC by a using symbiotic culture currently continues to broaden, including that for technical applications [ 25 , 44 , 45 , 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Benefiting from the advantages of biosynthesis and the characteristics of cellulose-based composite materials, these BC-based materials achieve better sustainability throughout the entire life cycle than plastics, from raw material processing to final product disposal. , Just like the process from the construction to natural degradation of biological materials, such sustainable life cycle is mainly embodied in the renewable raw materials, the low energy consumption and carbon emission of the production process, low environmental impact during use, and the natural degradability of final products.…”
Section: Characteristics Of the Aerosol-assisted Biosynthesis Strategymentioning
confidence: 99%
“…Studies related to life cycle assessment of the BC production process by static culture have been demonstrated that water is the main resource used (36 ton/kg), followed by the production of raw material (18 ton/kg), carton packs (14 ton/kg), and fermentation process (4 ton/kg). Of this total, about 98% are recovered after treatment; in addition, few environmental impacts were identified, especially when industrial waste was used as raw material [22, 31].…”
Section: Global Bc Marketmentioning
confidence: 99%
“…BC purification processes require lower energy amount than that required for other cellulosic materials—mainly due to its purity—and it enables reducing processing costs [21]; for example, considering an industry with capacity to produce 500 tons BC per year, the electric power consumption is estimated at around 360 kWh [22]. Besides that, BC purification generally requires nonaggressive chemicals at room temperature, such as sodium hydroxide, hydrogen peroxide, and/or sodium hypochlorite [23].…”
Section: Introductionmentioning
confidence: 99%